2016
DOI: 10.1155/2016/3042531
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Diffuse Large B Cell Lymphoma of Uterine Cervix Treated at a Semiurban Cancer Centre in North India

Abstract: Lymphoma of the uterine cervix is very rare. We report a case of diffuse large B cell lymphoma (DLBCL) involving the uterine cervix treated at a newly commissioned semiurban cancer centre in north India in 2015. Data for this study was obtained from the hospital electronic medical records and the patient's case file. We also reviewed published case reports of uterine and cervical lymphoma involving forty-one patients. We treated a case of stage IV DLBCL cervix with six cycles of R-CHOP (rituximab, cyclophospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In cervical cytology, the detection rate for malignant lymphoma cells has been reported to be 30%-40% [9]. Some researchers described that unlike epithelial tumor, lymphomas arise from the stroma, and that cervical cytology is not sensitive enough to recognize them [3]. However, in our case, the classical cervical cytological features of a malignant lymphoma from the conventional smear were so prominent; that we were able to detect the malignant lymphoma at an early stage from the cervical cytology.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In cervical cytology, the detection rate for malignant lymphoma cells has been reported to be 30%-40% [9]. Some researchers described that unlike epithelial tumor, lymphomas arise from the stroma, and that cervical cytology is not sensitive enough to recognize them [3]. However, in our case, the classical cervical cytological features of a malignant lymphoma from the conventional smear were so prominent; that we were able to detect the malignant lymphoma at an early stage from the cervical cytology.…”
Section: Discussionmentioning
confidence: 50%
“…Malignant lymphomas can also affect extra-nodal sites, approximately in one-third of the cases [3]; the most common sites are the gastrointestinal tract and skin [3]. In rare cases, it may affect the female reproductive organs, with the ovaries being the most common site [3], PLUCX is an extremely rare occurrence. As per MEDLINE, since the 1980s, about 250 cases of PLUCX have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Primary extra-nodal NHL of the uterine cervix is extremely rare. The uterine cervix was previously identified to be involved in one out of 730 cases of NHL and one out of 175 cases of extra-nodal lymphoma (1). Primary MS of the uterine cervix is additionally uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Case 5 was diagnosed with an advanced stage cancer with BM involvement; BM and a peripheral blood smear demonstrated the presence of myeloblasts was <20% and therefore, AML was not diagnosed and primary MS was considered. The majority of cervical lymphomas, as determined by histological examination, are DLBCL with diffuse infiltration of atypically large lymphoid cells (1). IHC staining demonstrated that cells were positive for LCA, CD20, Bcl-2, Bcl-6 and MUM1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation